2013
DOI: 10.1016/j.cell.2013.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of TET2-DNA Complex: Insight into TET-Mediated 5mC Oxidation

Abstract: TET proteins oxidize 5-methylcytosine (5mC) on DNA and play important roles in various biological processes. Mutations of TET2 are frequently observed in myeloid malignance. Here, we present the crystal structure of human TET2 bound to methylated DNA at 2.02 Å resolution. The structure shows that two zinc fingers bring the Cys-rich and DSBH domains together to form a compact catalytic domain. The Cys-rich domain stabilizes the DNA above the DSBH core. TET2 specifically recognizes CpG dinucleotide and shows sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
489
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(515 citation statements)
references
References 74 publications
22
489
1
3
Order By: Relevance
“…We next determined whether TET2 repression is associated with growth inhibitory effect of TET2 in prostate cancer. We also demonstrated that TET2 growth inhibitory ability was associated with the C-terminal domain important for its enzymatic activity 27 ( Supplementary Fig. 9).…”
Section: Resultsmentioning
confidence: 67%
“…We next determined whether TET2 repression is associated with growth inhibitory effect of TET2 in prostate cancer. We also demonstrated that TET2 growth inhibitory ability was associated with the C-terminal domain important for its enzymatic activity 27 ( Supplementary Fig. 9).…”
Section: Resultsmentioning
confidence: 67%
“…Although Methylcytosine can be modified to hydroxymethylcytosine by the Tet family of dioxygenases, Tet1-3. Current evidence demonstrates that the oxidative conversion of methylcytosine to hydroxymethylcytosine by the Tet enzymes occurs at CG dinucleotides, as is consistent with the overwhelming proportion of hydroxymethylation occurring as hmCG rather than hmCH (8,37). Additionally, Tet enzymes are capable of catalyzing further oxidation of hmC to formylcytosine and carboxylcytosine to yield substrates for Tdg, ultimately resulting in the generation of a nonmethylated cytosine (10,11).…”
mentioning
confidence: 76%
“…Indeed, given that few individual genomic sites exhibit significant levels of CH hydroxymethylation (hmCH), it remains unclear whether hmCH exists as a genuine species in vivo. Recent characterization of the Tet enzymes has demonstrated a strong preference for oxidation of mCG compared with mCH, providing a possible explanation for the low levels of hmCH (37). However, these steady-state measurements do not rule out the possibility that hmCH is turned over rapidly after conversion from mCH.…”
mentioning
confidence: 83%
“…Additionally, TET enzymes may prefer CG sites (Hu et al 2013) which raises the intriguing possibility that mCH may be resistant to oxidation and elimination. Our understanding of the effects of mC/hmC on gene expression and genome organization with aging is in its infancy.…”
Section: Nature and Regulation Of Dna Modificationsmentioning
confidence: 99%